Creatures of attention : aesthetics and the subject before Kant - Wankhammer, Johannes, 1982- (Ithaca, New York : Cornell University Press and Cornell University Library, 2024)
"The book examines the discourse on attention emerging in the European Enlightenment (1650-1780) with a focus on German philosophy and literature. It argues that this discourse influenced the formation of aesthetic philosophy in the eighteenth century. Notable figures discussed include René Descartes, G.W.F. Leibniz, Christian Wolff, and Alexander Baumgarten."--
Attention. Introducing a new faculty of the soul -- Science. Attention, the new science, and the disembodied mind -- Subject. Before the autonomous subject: disciplines of attention in the German eighteenth century -- Poetics. Wonder and the poetics of attention: poetry as education of attentiveness in B. H. Brockes and J. J. Breitinger -- Aesthetics. Attending to the margins: Baumgarten's unredeemed foundation of aesthetics -- Afterlives. Modulations of attention since 1800.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on May 22, 2024).
JSTOR
Keywords: Attention -- Philosophy; Subjectivity; Aesthetics, Modern -- 18th century; Autonomy (Philosophy); Philosophy, German -- 18th century; German literature -- 18th century -- History and criticism; Attention -- Philosophie; Esthétique -- 18e siècle.; Autonomie (Philosophie); Philosophie allemande -- 18e siècle.; Littérature allemande -- 18e siècle -- Histoire et critique; PHILOSOPHY / Aesthetics; Philosophy: metaphysics & ontology; Philosophy; Electronic books